ZOONOTIC DISEASE OUTBREAKS IN KERALA- CAUSES, TRENDS AND MITIGATION STRATEGIES - Dr.Jinchu K Raju (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Zoonotic diseases are a significant public health challenge worldwide, with Kerala, a picturesque state in southwest India, experiencing an increase in the incidence of these diseases. This paper analyses the causes of the increase in zoonotic diseases in Kerala between 2018 and 2023 on a multifaceted basis. A number of factors contribute to the emergence and resurgence of these diseases, such as ecological changes, habitat destruction, climate variability, animal trade, and improper food practices. There is a clear emphasis in the study on the importance of wildlife conservation, sustainable land management, animal trade regulation, public awareness campaigns, a One Health approach, research and surveillance, vector control, occupational safety and health measures, community engagement, and government support in mitigating the impact of zoonotic diseases. By implementing these, Kerala can serve as a valuable case study, revealing insights and making recommendations for other states facing similar challenges, emphasizing the importance of collaborative efforts and proactive measures for ensuring the protection of public health and biodiversity.